Adaptation of Saccharomyces cerevisiae cells to high ethanol concentration and changes in fatty acid composition of membrane and cell size. - Thai Nho Dinh (Public Library of Science (PLoS), 2008)
Background Microorganisms can adapt to perturbations of the surrounding environment to grow. To analyze the adaptation process of the yeast Saccharomyces cerevisiae to a high ethanol concentration, repetitive cultivation was performed with a stepwise increase in the ethanol concentration in the culture medium. Methodology/principal findings First, a laboratory strain of S. cerevisiae was cultivated in medium containing a low ethanol concentration, followed by repetitive cultivations. Then, the strain repeatedly cultivated in the low ethanol concentration was transferred to medium containing a high ethanol concentration and cultivated repeatedly in the same high-ethanol-concentration medium. When subjected to a stepwise increase in ethanol concentration with the repetitive cultivations, the yeast cells adapted to the high ethanol concentration; the specific growth rate of the adapted yeast strain did not decrease during repetitive cultivation in the medium containing the same ethanol concentration, while that of the non-adapted strain decreased during repetitive cultivation. A comparison of the fatty acid composition of the cell membrane showed that the contents in oleic acid (C(18:1)) in ethanol-adapted and non-adapted strains were similar, but the content of palmitic acid (C(16:0)) in the ethanol-adapted strains was lower than that in the non-adapted strain in media containing ethanol. Moreover, microscopic observation showed that the mother cells of the adapted yeast were significantly larger than those of the non-adapted strain. Conclusions Our results suggest that activity of cell growth defined by specific growth rate of the yeast cells adapted to stepwise increase in ethanol concentration did not decrease during repetitive cultivation in high-ethanol-concentration medium. Moreover, fatty acid content of cell membrane and the size of ethanol-adapted yeast cells were changed during adaptation process. Those might be the typical phenotypes of yeast cells adapted to high ethanol concentration. In addition, the difference in sizes of the mother cell between the non-adapted and ethanol strains suggests that the cell size, cell cycle and adaptation to ethanol are thought to be closely correlated.